Probability concepts and theory for engineers - Schwarzlander, Harry (Chichester, West Sussex : John Wiley & Sons, 2011)
'This book aims to get the electrical and electronic engineering student well versed in the'machinery' of probability theory. It steers clear of getting into application areas any more than is needed to get the reader comfortable with the mathematics and connecting it to models of practical situations. The author has elaborated and expanded upon his teaching notes, developed over a number of years with feedback from his students. Classroom tested, this book should cover everything that is required by the electrical engineering student of today, and with a solutions manual accompanying, the book will be perfect for teaching purposes. First book aimed specifically at electrical and electronic engineering graduates to adequately explain the basic models and rules for applying probability theory to engineering Unique presentation- 86 Sections, each ending with short-answer review questions, are divided into 6 Parts making the material easy to teach and also suitable for self-study Over 600 problems in the Appendix, and a separate solutions manual Includes more challenging material on fuzziness, entropy, singular random variables and copulas, encouraging further study into the area and providing a refresher for practicing and researching engineers'--Provided by publisher.
'This book aims to get the electrical and electronic engineering student well versed in the 2018machinery' of probability theory'--
Includes bibliographical references and index.
Keywords: Probabilities; Electrical engineering -- Mathematics